The role of three-dimensional imaging in optimizing diagnosis, classification and surgical treatment of hepatocellular carcinoma with portal vein tumor thrombus. Issue 3 (March 2016) - Wei, Xu-Biao; Xu, Jie; Li, Nan; Yu, Ying; Shi, Jie; Guo, Wei-Xing; Cheng, Hong-Yan; Wu, Meng-Chao; Lau, Wan-Yee; Cheng, Shu-Qun
Abstract: Background: Accurate assessment of characteristics of tumor and portal vein tumor thrombus is crucial in the management of hepatocellular carcinoma. Aims: Comparison of the three-dimensional imaging with multiple-slice computed tomography in the diagnosis and treatment of hepatocellular carcinoma with portal vein tumor thrombus. Method: Patients eligible for surgical resection were divided into the three-dimensional imaging group or the multiple-slice computed tomography group according to the type of preoperative assessment. The clinical data were collected and compared. Results: 74 patients were enrolled into this study. The weighted κ values for comparison between the thrombus type based on preoperative evaluation and intraoperative findings were 0.87 for the three-dimensional reconstruction group (n = 31) and 0.78 for the control group (n = 43). Three-dimensional reconstruction was significantly associated with a higher rate of en-bloc resection of tumor and thrombus ( P  = 0.025). Using three-dimensional reconstruction, significant correlation existed between the predicted and actual volumes of the resected specimens (r = 0.82, P  < 0.01), as well as the predicted and actual resection margins (r = 0.97, P  < 0.01). Preoperative three-dimensional reconstruction significantly decreased tumor recurrence and tumor-related death, with hazard ratios of 0.49 (95% confidential interval, 0.27–0.90) and 0.41 (95% confidential interval, 0.21–0.78), respectively. Conclusion: For hepatocellular carcinoma with portal vein tumor thrombus, three-dimensional imaging was efficient in facilitating surgical treatment and benefiting postoperative survivals.